Unconscious bias in employee management: evolving with emotional intelligence development - Nixon, Rachel A. (University of Wisconsin--Stout, 2019)
In this paper, there is a comprehensive discussion on unconscious bias that can be experienced in employee management. The elements of company culture are as diverse as the employees who comprise it, with various behavior, emotions, and thought patterns that become the norm for the company. As a company culture develops, conscious and unconscious bias can influence how organizational leaders manage personnel. The primary purpose of this study was to find the best unconscious bias training practices in United States organizations. The current literature on bias training was reviewed and applied to the research conducted in this study. Finally, best unconscious bias training practices are evaluated and comprised into a training outline.
Keywords: Employees; Emotional intelligence; Work environment